A door in the earth - Waldman, Amy, 1969- (Little, Brown and Company, 2019)
Parveen Shams, a college senior in search of a calling, feels pulled between her charismatic and mercurial anthropology professor and the comfortable but predictable Afghan-American community in her Northern California hometown. When she discovers a bestselling book called Mother Afghanistan, a memoir by humanitarian Gideon Crane that has become a bible for American engagement in the country, she is inspired. Galvanized by Crane's experience, Parveen travels to a remote village in the land of her birth to join the work of his charitable foundation. When she arrives, however, Crane's maternity clinic, while grandly equipped, is mostly unstaffed. The villagers do not exhibit the gratitude she expected to receive. And Crane's memoir appears to be littered with mistakes, or outright fabrications. As the reasons for Parveen's pilgrimage crumble beneath her, the U.S. military, also drawn by Crane's book, turns up to pave the sole road to the village, bringing the war in their wake. When a fatal ambush occurs, Parveen must decide whether her loyalties lie with the villagers or the soldiers -- and she must determine her own relationship to the truth.